A 3‐D analytic eddy current model for a finite width conductive plate. Issue 1 (2014) - ,; ,
Abstract : Purpose – A 3‐D analytic modeling technique for calculating the eddy current distribution, force and power loss in a conductive plate of finite width and thickness is presented. The derived equations are expressed in a general form so that any magnetic source can be utilized. The model assumes the length of the conductive plate is large and the thickness of the plate is thin but not negligible. The paper aims to discuss these issues.Design/methodology/approach – The conducting and non‐conducting regions are formulated in terms of decoupled magnetic vector potential components. In order to accurately compute the eddy current fields and forces the source field only needs to be applied on the surface of the conducting plate. The primary focus is on reducing the eddy current computational time.Findings – The accuracy of the presented approach is verified by utilizing a magnetic rotor that has both a rotational and translational motion. The proposed method is computationally efficient and its accuracy is validated using the finite element method.Research limitations/implications – The conducting plate thickness is assumed to be thin (but not negligible), and this enables the field interaction through the edge of the plate to be neglected. The lateral force is not calculated in the proposed approach.Practical implications – The calculation procedure presented is computationally fast and therefore this can enable the 3‐D eddy current forces to be computed in near real‐time.Originality/value – This paper presents a fully 3‐D analytic based eddy current formlation for computing the eddy current fields and forces in a conducting plate of finite thickness and finite width. The modeling approach is shown to be computationally accurate and relatively fast. Acknowledgements : The authors would gratefully like to thank the JMAG Corporation for the use of their finite element analysis software. This material is based upon work supported by the National Science Foundation under Grant No. 0925941.